2008
DOI: 10.2134/agronj2007.0007
|View full text |Cite
|
Sign up to set email alerts
|

Rice Growth, Grain Yield, and Floodwater Nutrient Dynamics as Affected by Nutrient Placement Method and Rate

Abstract: Th e loss of major nutrients can be high in rice (Oryza sativa L.) fi elds, particularly rainfed rice, where water fl owing from fi eld to fi eld during periods of high rainfall not only reduces the nutrient use effi ciencies but also has the potential for environmental degradation. We examined the infl uence of deep point placement of N, P, and K briquettes compared to broadcast incorporation of N, P, and K on fl oodwater nutrient loads aft er fertilizer application and on the performance of wet season rice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
53
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 11 publications
13
53
1
Order By: Relevance
“…The increase in rice yield as observed in the present study is due to the spontaneous supply of nitrogen from USG throughout the growing period of rice and due to minimum loss of nitrogen as because of deep placement. These findings are well corroborated with Kapoor et al (2008), Islam et al (2011), and Afroz et al (2014) and Huda et al (2016) who observed increased rice yield due to application of USG and NPK briquettes. Islam et al (2014) also reported that grain yield of BRRI dhan28 increased by 97.03% over control with the application of USG and 87.58% with NPK briquette whereas 66.24% grain yield increase was obtained with PU application.…”
Section: Grain Yieldsupporting
confidence: 83%
See 1 more Smart Citation
“…The increase in rice yield as observed in the present study is due to the spontaneous supply of nitrogen from USG throughout the growing period of rice and due to minimum loss of nitrogen as because of deep placement. These findings are well corroborated with Kapoor et al (2008), Islam et al (2011), and Afroz et al (2014) and Huda et al (2016) who observed increased rice yield due to application of USG and NPK briquettes. Islam et al (2014) also reported that grain yield of BRRI dhan28 increased by 97.03% over control with the application of USG and 87.58% with NPK briquette whereas 66.24% grain yield increase was obtained with PU application.…”
Section: Grain Yieldsupporting
confidence: 83%
“…Again, the deep placement of USG and NPK briquette minimizes the concentration of NH 4 -N in floodwater compared to broadcast application of PU. Kapoor et al (2008) reported that broadcast application of N as urea resulted on an average 10 times higher amounts of ammonium N in flood water compared to deep placement of urea briquette and NPK briquette. Bhuiyan et al (1998) reported that deep point placement of USG produced significantly higher grain yield of rice than split application of PU.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is the main nutrient associated with yield, but N management responds differently to rice type (indica or japonica associated with climate requirement and interaction with N nutrition), cultivar, geographic zone, and other crop practices (Angus et al, 1994;Ying et al, 1998;Bouman et al, 2007;De-Xi et al, 2007;Huang et al, 2008;Jing et al, 2008;Hirzel et al, 2011a). Similarly, fertilization management and genotype × environment interaction generate differences in plant nutrient composition (Mengel and Kirkby, 1987); they affect crop extraction, rice plant yield components, and N use efficiency (Ying et al, 1998;Kapoor et al, 2008;Matsunami et al, 2009;Taylaran et al, 2009). At the same time, differences in nutrient compartmentalization in the rice plant (grain and residues) (Cordero-Vásquez and Murillo- Vargas, 1990) produce positive or negative effects on the nutrient balance of the soil-plant system for those productive systems in which plant residues are incorporated or extracted.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the treatment comparisons, the benefits to the vegetables crops can largely be attributed to the deep placement of NPK briquettes. Kapoor et al (2008) and Islam et al (2011) observed significantly higher N, P, and K uptake with deep placement of NPK briquette compared to broadcast application. The positive impact of cowdung is evident for higher yield, nutrient uptake, and nutrient recovery when compare the NPK briquette with cowdung (T 6 ) and NPK briquette without cowdung (T 7 ).…”
Section: Figures In a Column Having Common Letters Do Not Differ Signmentioning
confidence: 91%